Control interno y su incidencia en los proveedores del comercial Joselito del cantón Baba - Cuaical Cajas, Juan Carlos (2021)
Commercial Joselito is located in Baba Canton, Los Ríos Province, providing commercial level services, offering citizens basic articles and products; also functioning as a bazaar due to the large number of products and services offered. The need for a control system has been observed, both for inventories, products and suppliers, since the system currently applied is presenting drawbacks, generating loss of credibility and dissatisfaction in customers. Internal Control within the company is focused on the development of activities, which will allow us to achieve the objectives set, thus reducing irregularities or incidents that may arise in the commercial field. The need arises to provide a solution to this problem presented on the relationship between suppliers and commercial, in order that the parties involved are working in harmony and competently. The evaluation of internal control within the company will allow us to analyze how effective its systems are, whether accounting or administrative.